The Effect of Court Footwork Applications and Conventional Exercises on Badminton Footwork - Yogi Slamet; Herman Subarjah; Dewi Susilawati (STKIP Muhammadiyah Kuningan, 2022)
This research stems from the findings in the field that athletes experience many difficulties in footwork movements. This study aimed to determine the significant influence between technology and conventional. The method used is a quasi-experimental design with a pre-test and post-test group design. This study showed an increase in using the CF application of as much as 16.27%, with a pre-test value of 48.80% and a post-test value of 65.07%. And conventional exercise had an increase of 12.80%, with a pre-test value of 64.53% and a post-test of 77.33%. This shows a superior difference of 3.47% using the CF application compared to conventional. Thus, it can be concluded that the practice of CF and Conventional applications can affect the footwork ability of Badminton Players at UKM Badminton UPI Sumedang.